2014
DOI: 10.5888/pcd11.130221
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Adoption of a Patient Education Intervention Among First Responders, King County, Washington, 2010–2011

Abstract: IntroductionThis study investigated facilitators and barriers to adoption of an at-scene patient education program by firefighter emergency medical technicians (EMTs) in King County, Washington.MethodsWe consulted providers of emergency medical services (EMS) to develop a patient education pamphlet in the form of a tear-off sheet that could be attached to the EMT medical incident report. The pamphlet included resources for at-scene patient education on high blood pressure, blood glucose, falls, and social serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…King County in Washington State utilized firefighter–EMTs and found that non-transported patients were receptive to a health education program. 19 These EMTs provided four types of health information that included a referral source for fall prevention programs. Wake County EMS providers have also developed a program to manage falls in skilled nursing facilities.…”
Section: Discussionmentioning
confidence: 99%
“…King County in Washington State utilized firefighter–EMTs and found that non-transported patients were receptive to a health education program. 19 These EMTs provided four types of health information that included a referral source for fall prevention programs. Wake County EMS providers have also developed a program to manage falls in skilled nursing facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because EMS programs are typically emergency-services-oriented, EMS leadership must endorse a more preventive role to allow for a shift in the traditional paradigm to occur. Adoption of this new role by EMTs depends on leadership buy-in, encouragement, and change in perceptions of an expanded mission of EMS (10). …”
Section: Discussionmentioning
confidence: 99%
“…A tear-off sheet with information about the locally available programs was developed specifically for the project with input from EMS advisors (Figure 1) (10). One program was a home-based program; the other was a falls assessment clinic operating at the county hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Although the information left at the scene statistically increased enrollment of people in a fall prevention program, fewer than 35% of individuals given the information reported that they had EMS discuss falls with them at the time of 911 call, and only 3% more individuals given the information than in the control group enrolled in fall‐prevention programs. Although only a few individuals enrolled in a fall‐prevention program after EMS education after a fall, this strategy was cost effective, was supported by EMS providers, and has the potential to create a new pathway for activating fall prevention strategies and education . These concepts build on the SAFER trials performed in the United Kingdom that concluded that involving EMS in fall reduction strategies is feasible and effective, but further work on timing of the intervention, whether to activate fall prevention strategies and education at the scene or at a later date, may prove to be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a few individuals enrolled in a fall-prevention program after EMS education after a fall, this strategy was cost effective, was supported by EMS providers, and has the potential to create a new pathway for activating fall prevention strategies and education. 35,36 These concepts build on the SAFER trials performed in the United Kingdom that concluded that involving EMS in fall reduction strategies is feasible and effective, but further work on timing of the intervention, whether to activate fall prevention strategies and education at the scene or at a later date, may prove to be more effective. Comprehensive systemlevel strategies that help coordinate care among care providers, individuals, and community programs may help change the paradigm of care for older adults and bridge some of the gaps in fall prevention strategies for older adults.…”
Section: Discussionmentioning
confidence: 99%